The Internationalization of the Indonesian Language: Promotion and Its Application in the Global Arena - Ya Panting; Kaharuddin Kaharuddin; Wang Man; Munira Hasjim; Ikhwan M. Said; Andi Merling (Journal of Innovative and Creativity (Joecy), 2026)
In the era of rapid globalization, language plays a crucial role as a medium of communication and cultural interaction. Indonesian, the official language of the Republic of Indonesia, not only serves as a symbol of national identity but also has the potential to act as a bridge in international contexts. The promotion of Indonesian in the global sphere has garnered significant attention, especially given Indonesia’s rapid economic growth and increasing cultural influence worldwide. With advancements in information and communication technology, opportunities for promoting Indonesian have expanded. Social media, online educational platforms, and cultural activities have become effective channels for introducing Indonesian language and culture to international audiences. However, the globalization of Indonesian faces challenges such as the dominance of English, dialectal variations, and disparities in access to language education. This study aims to analyze the dynamics of the globalization of Indonesian, its promotion, and its application on the international stage. By understanding current conditions, identifying challenges, and proposing future strategies, the study seeks to ensure the relevance and widespread use of Indonesian globally.